Circling the Giant Tree: A Response to Andrew Meyer and Dennis Schilling. - Vermander, Benoît (Dao: A Journal of Comparative Philosophy, 2023)
The present article discusses remarks and suggestions made by Andrew Meyer and Dennis Schilling on a previous contribution of the author. It assesses the status of the root-branches analogy in the Huainanzi 淮南子, and the compatibility of the said analogy with the composition of the same work as a ring composition. It also discusses the numerology proper to the Huainanzi in view of the principles provided by the Yijing 易經. It compares the structural arrangements of the Huainanzi with the ones found in the various versions of the Daodejing 道德經. It concludes on the relationship that these two works establish between the understanding the Way (dao 道) and knowledge about shapes and numbers.